Effects of grinding media on the material properties and strengthening mechanism of silicon production. (1st January 2021) - Zhou, Shichao; Chen, Zhengjie; Ma, Wenhui; Li, Shaoyuan; Yang, Xi; Cao, Shijie
Abstract: In this study, we evaluated the characteristics and applications of carbonaceous materials, which play a vital role in silicon production. Specifically, we conducted an exploratory study on biomass and petroleum coke (PC) performance improvement in response to different grinding media, and discussed the outcomes of our experimental results in conjunction with thermodynamic and kinetic analysis. Furthermore, we comprehensively analyzed the strengthening mechanism using Fourier-transform infrared (FTIR) spectroscopy, Raman spectroscopy, and scanning electron microscopy (SEM). The results showed that the initial reduction reaction temperature was significantly lowered by using the wet-grinding method. Even more remarkably, the maximum reaction rate increased from 62% to 157% when organic solvent was added to the mixture during the wet-grinding process and the proportion of decreased activation energy increased from 15.34% to 22.35%, as compared with dry-blending. Thus, the mixtures' reactivity improved by using wet-grinding, especially after adding organic solvent, which increased the carbothermic reduction utilization of PC and biomass. A potential primary cause may be related to the "like dissolves like" interaction between organic solvents and organic functional groups in carbon materials. This study has important implications for developing low-cost, low energy consumption of silicon, as well as promoting clean, efficient production. Highlights: Absolute ethyl alcohol was used as cosolvent. The effect of grinding media on the reaction properties of materials was studied. Strengthening smelting mechanism of industrial silicon was analyzed.